Urban tourism - Page, Stephen, 1963- (Routledge, 1995)
This is the first introductory level text to look at the nature of urban tourism. A study of the issues and problems involved in urban tourism reveals the multifunctional nature of cities as tourist destinations. All the main aspects of urban tourism are examined including: the range of tourists and their motives for visiting urban destinations, the types of facilities, the impact of tourism on urban environments, and managerial and planning techniques used to market and manage cities as tourism destinations. Recent innovations in the management of urban tourism are highlighted. A range of international case studies provide practical examples of the issues raised. This integrated, holistic view of urban tourism encompasses the needs of practitioners, and will be very useful for students of tourism, leisure and planning at diploma and undergraduate level.